Raman light scattering in pseudospin-electron model at strong pseudospin-electron interaction - Mysakovych, T.S.; Stasyuk, I.V. (Condensed Matter Physics, 2004)
Anharmonic phonon contributions to Raman scattering in locally anharmonic crystal systems in the framework of the pseudospin-electron model with tunneling splitting of levels are investigated. The case of strong pseudospin-electron coupling is considered. Pseudospin and electron contributions to scattering are taken into account. Frequency dependences of Raman scattering intensity for different values of model parameters and for different polarization of scattering and incident light are investigated. Досліджено ангармонічні фононні внески до комбінаційного розсіяння світла у локально-ангармонічних кристалічних системах в рамках псевдоспін-електронної моделі з тунельним розщепленням рівнів. Розглянено випадок сильної псевдоспін-електронної взаємодії. Враховано псевдоспінові та електронні внески в розсіяння. Досліджено частотну залежність інтенсивності комбінаційного розсіяння світла при різних значеннях параметрів моделі та при різних співвідношеннях між поляризацією падаючого та розсіяного світла.